Correction of complex nonlinear signal response from a pixel array detector. (21st April 2015) - van Driel, Tim Brandt; Herrmann, Sven; Carini, Gabriella; Nielsen, Martin Meedom; Lemke, Henrik Till
<x xml:space="preserve">Abstract</x> The pulsed free‐electron laser light sources represent a new challenge to photon area detectors due to the intrinsic spontaneous X‐ray photon generation process that makes single‐pulse detection necessary. Intensity fluctuations up to 100% between individual pulses lead to high linearity requirements in order to distinguish small signal changes. In real detectors, signal distortions as a function of the intensity distribution on the entire detector can occur. Here a robust method to correct this nonlinear response in an area detector is presented for the case of exposures to similar signals. The method is tested for the case of diffuse scattering from liquids where relevant sub‐1% signal changes appear on the same order as artifacts induced by the detector electronics.